SMARTPHONES: A SCHOOL IN THE DIGITAL INFORMATION ERA OF THE 21ST CENTURY (VERUM: Journal of Scientific Initiation, 2022)
This paper presents a discussion on the use of mobile technologies at the Application School of the Federal University of Roraima, compared to the actions of the municipal and state levels of the state of Roraima during the COVID-19 pandemic in the first semester of 2020. Thus, we sought to analyze how the Application School (CAp) attempted to solve problems related to the lack of access faced by students in social vulnerability due to the social distancing caused by the state of health emergency in Brazil. The research utilized sources from local and institutional newspaper websites, as well as a bibliographic review of articles and books to compare data and provide the research conclusion on the topic.
Keywords: Application School; ICTs; Social Vulnerability